Are IPOs of Different VCs Different? - Tereza Tykvová; Uwe Walz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
This paper sets out to analyze the influence of different types of venture capitalists on the performance of their portfolio firms around and after IPO. We investigate the hypothesis that different governance structures, objectives, and track records of different types of VCs have a significant impact on their respective IPOs. We explore this hypothesis using a data set embracing all IPOs that have occurred on Germany's Neuer Markt. Our main finding is that significant differences among the different VCs exist. Firms backed by independent VCs perform significantly better two years after IPO as compared to all other IPOs, and their share prices fluctuate less than those of their counterparts in this period of time. On the contrary, firms backed by public VCs show relative underperformance. The fact that this could occur implies that market participants did not correctly assess the role played by different types of VCs.
Keywords: G32; G24; G14; 330; Venture Capital; Initial Public Offerings; Long-Run Performance; Underpricing; Heterogeneity; Wertpapieremission; Risikokapital; Corporate Governance; Börsenkurs; Unternehmensentwicklung; Schätzung; Neuer Markt; Deutschland